Triple Threat: Spinal Dural Arteriovenous Fistula in Spinal Dysraphism and Tethered Cord Syndrome, a Case Report with Literature Review - Liew, Sarah Ileen; Thanabalan, Jegan; Soon, Bee Hong; Zakaria, Rozman (Journal Of Cardiovascular, Neurovascular & Stroke, 2023)
Introduction: The incidence of spinal dural arteriovenous fistula (SDAVF) in patients with spinal dysraphism is exceedingly rare with fewer than 30 cases reported. We report such a case and discuss the etiology, diagnostic, and treatment challenges of such patients. Case Presentation: This is a 37-year-old gentleman with a history of myelomeningocele (MMC) repair at the age of 2 years who presented to us with worsening bilateral lower limb weakness and numbness. Clinical examination demonstrated affected motor and sensory functions from the level of L2. An MRI Lumbosacral revealed S3/S4 dysraphism with a tethered low-lying conus. A CT angiogram of the spine followed by a spinal angiogram confirmed the diagnosis of a SDAVF with feeders from the median sacral artery and other branches of the left internal iliac artery. He underwent angioembolization, following which we noted a residual SDAVF and hence underwent a difficult second-stage angioembolization to the right lateral sacral artery branch. The patient remained status quo on follow-up. Conclusion: SDAVFs occurring in spinal dysraphism requires a high index of suspicion to ensure the diagnosis is not missed or masked by co-existing tethered cord and dysraphism. These lesions should be managed in a multidisciplinary multimodal individualized fashion.